2017
DOI: 10.1080/19336950.2017.1370525
|View full text |Cite
|
Sign up to set email alerts
|

PKC SUMOylation inhibits the binding of 14–3–3τ to GluK2

Abstract: Phosphorylation and SUMOylation of the kainate receptor (KAR) subunit GluK2 have been shown to regulate KAR surface expression, trafficking and synaptic plasticity. In addition, our previous study has shown that a phosphorylation-dependent interaction of 14-3-3t and GluK2a-containing receptors contributes to the slow decay kinetics of native KAR-EPSCs. However, it is unknown whether SUMOylation participates in the regulation of the interaction between 14-3-3t and GluK2a-containing receptors. Here we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…More recently, the same group also reported that SUMOylation of PKC inhibits the binding of 14–3‐3tau to GluK2 by reducing GluK2 phosphorylation (Li, Wang, Zhu, Zhou, & Li, 2017). 14–3‐3tau is a conserved family of regulatory proteins that bind to a wide range of targets, and binding to GluK2 contributes to the slow decay kinetics of KAR‐mediated excitatory post‐synaptic currents (EPSCs) (Sun et al., 2013).…”
Section: Expression and Compartmentalization Of Sumoylation And Desummentioning
confidence: 98%
“…More recently, the same group also reported that SUMOylation of PKC inhibits the binding of 14–3‐3tau to GluK2 by reducing GluK2 phosphorylation (Li, Wang, Zhu, Zhou, & Li, 2017). 14–3‐3tau is a conserved family of regulatory proteins that bind to a wide range of targets, and binding to GluK2 contributes to the slow decay kinetics of KAR‐mediated excitatory post‐synaptic currents (EPSCs) (Sun et al., 2013).…”
Section: Expression and Compartmentalization Of Sumoylation And Desummentioning
confidence: 98%